Illocutionary Acts by Zelensky in Meeting Donal Trump on the Russia-Ukraine War. - Agustinus Abat; I Dewa Ayu Devi Maharani Santika (Universitas Islam Negeri Palopo, 2025)
Illocutionary acts are crucial elements in both formal and informal communication, particularly in political discourse where language functions as a strategic instrument. This study examines the illocutionary acts used by President Volodymyr Zelensky during his meeting with President Donald Trump on February 28, 2025, in the context of the ongoing Russia–Ukraine war. The main objective is to identify the types of speech acts employed and to interpret how they reflect Zelensky’s diplomatic intentions. This study adopts a descriptive qualitative method, with data collected from the meeting’s video and transcript through observation and note-taking techniques. The analysis applies Yule’s (1996) classification of illocutionary acts, consisting of representative, directive, commissive, expressive, and declarative types. The findings reveal four types of illocutionary acts, representative (54 data), directive (11 data), commissive (7 data), and expressive (7 data), with representatives emerging as the most dominant. These acts were mainly used to describe Ukraine’s situation and emphasize the necessity of strong security guarantees. The results contribute to the understanding of how political leaders employ language not only to communicate but also to negotiate, persuade, and build diplomatic trust. Unlike previous research focused on campaign or victory speeches, this study provides new insights into how illocutionary acts operate in high-level diplomatic communication during international conflict.